(Re)turning to practice in teacher education: embodied knowledge in learning to teach. Issue 1 (2nd January 2017) - Mathewson Mitchell, Donna; Reid, Jo-Anne
Abstract: Contemporary research conversations about the utility of practice theories to professional education support the reconceptualisation of pre-service teacher education in ways that provide strong preparation for continued professional learning. This paper reports on an empirical inquiry that introduced a theoretically informed practice-based intervention in a pre-service teacher education course in order to judge the utility of such an approach for student learning. Innovations within the Study of Teaching programme illustrate the bringing together of pedagogies of observation, pedagogies of enactment, and pedagogies of reflection toward an integrated theory of teacher education that focuses on the teaching body as a central site for research and for the building of preparatory knowledge and skill for ongoing learning. Data was collected from pre-service teachers involved in the programme through video and audio recordings along with individual and focus group interviews, questionnaires and student reflection on video recordings. These were analyzed within an emerging theoretical framework derived from both practice-theoretical literature and international empirical research into core practices. Initial findings suggest that a focus on practice within pre-service teacher education may enhance traditional understandings of 'practice-based' approaches that situate the study of practice outside of the university, in school settings. These findings have implications for the ongoing reform of teacher education in increasingly regulated contexts framed in terms of teacher quality.